Intrusion identification system using domain name service - Mohamad Rais, Faisal (2008)
This research intends to investigate and research to a detection to be used on the internet security. A study is done by IIS identifying whether Intrusion Detection System protect domain service services from cache poisoning and denial of service. Currently, there are few types of DNS Cache Poisoning which are redirecting the DNS of the attacker to targeted DNS which later attacker assigns an IP to that particular DNS, Redirecting the Name Server to a new unrelated IP specified by attacker, DNS Forgery, Recursive DNS query to DNS Server to beat the real DNS query, Predicting 16-bit nuances in recursive method (Birthday Attack). It also improving computer or server is the move to increase protection against theft or corruption from internal or external threat. In other hand it also protects the data storage that needs to be secured from preying eyes. Limiting user from visiting unauthorized areas is also some of the reasons improving security of a system is crucial. The menace of not monitoring a security of a system could lead to information leak; resource drain, modified information and many hacker activities plague the system operation. Improving security could be in aspect of hardware and software.